Os símbolos na obra Marta, a árvore e o relógio, de Jorge Andrade - Lazarotti, Adriane Abrantes (2016)
This dissertation analyzes the symbolism in Marta, a árvore e o relógiobook, writtenby Jorge Andrade in order to understand the symbolic link used among the parts of the cycle as well as realize the playwright used the symbols in the conventional manner or assigned new meanings to the them. The cycle of ten pieces of Jorge Andrade has, among many goals, the nationalization of Brazilian drama and give to marginalized voice, understanding them as an integral part of the story . The interpretative study 's main theoretical basis for the study of Brazilian dramaturgy Anatol Rosenfeld, Sabato Magaldi, Decio de Almeida Prado, João Roberto Faria, Mario Guidarini and for the study of symbolic Gaston Bachelard , Gilbert Durand, Mircea Eliade, Carl G. Jung, Pierre Bourdieu among others. The playwright chooses, among its main symbols , a symbol of freedom that is Marta to tell about the cycle and to fight for faceless . The tree, which not only is the genealogy, but also the connection with the transcendent, protection and life. And the clock without hands that refers to the time stopped in the air, the struggle of man against time and against history , which is always told from the viewpoint dominant and exclusionary. The way how Andrade sewing the history of Brazil, the various symbols present in his work and the genealogy of his characters reveal one of the greatest geniuses of Brazilian theater .